Uma Nova Metodologia para formação de Grupos em VANETs - Vieira, André; Farias, Claudio; Melo Jr., Wilson (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
This work proposes a new methodology to create groups in intervehicular networks as a basis for complex applications involving smart vehicles. We proposed a distributed protocol whose purpose is to build a higher number of groups in less time, keeping the vehicles grouped for most of their journey. We implement our proposal in two versions. The first one considers only the interaction among vehicles. The second includes a group merge functionality. We validate both versions of our protocol using simulation with real traffic data. We evaluate the amount of created groups and their persistence and size.